Identifying the challenges and opportunities to meet the needs of children with speech, language and communication difficulties. (30th January 2016) - Dockrell, Julie E.; Howell, Peter
Abstract : The views of experienced educational practitioners were examined with respect to the terminology used to describe children with speech, language and communication needs (SLCN), associated problems and the impact of speech and language difficulties in the classroom. Results showed that education staff continue to experience challenges with the range of terminology used to refer to the children's needs. Terms used to refer to difficulties with speech were least familiar to the respondents. Difficulties were noted in distinguishing between children with SLCN and children where English was an additional language. Respondents indicated a variety of additional difficulties experienced by the children. Literacy difficulties were reported to be more prevalent in children with language difficulties, while levels of bullying and anxiety were reported to be higher in children with speech problems. Respondents reported that tools for identifying speech and language difficulties and procedures for accessing effective resources are required.